2016
DOI: 10.1002/jat.3314
|View full text |Cite
|
Sign up to set email alerts
|

Dose site reactions and related findings after vaccine administration in safety studies

Abstract: Potential new human vaccines undergo toxicology testing to evaluate local reactogenicity and systemic toxicity. A review of 30 recently published and in-house repeat dose toxicity studies with a variety of vaccines was performed. Species tested were generally rat or rabbit, usually by intramuscular (although occasionally subcutaneous) injection. Results showed no unexpected findings indicating vaccine toxicity, but classic signs of enhanced acute and/or chronic inflammation at the dose site compared with that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Subcutaneous administration of ADP at MTD during 7 consecutive days was well tolerated. Injection site reactions were observed and attributed to the aluminum hydroxide as reported with other vaccines containing this adjuvant . Some hematological alterations were detected such as an increase in blood neutrophil count and globulin, and a decrease in albumin.…”
Section: Discussionmentioning
confidence: 65%
“…Subcutaneous administration of ADP at MTD during 7 consecutive days was well tolerated. Injection site reactions were observed and attributed to the aluminum hydroxide as reported with other vaccines containing this adjuvant . Some hematological alterations were detected such as an increase in blood neutrophil count and globulin, and a decrease in albumin.…”
Section: Discussionmentioning
confidence: 65%
“…ProteqFlu-Te®). 31 A dose of 2000 µg was then selected as a reasonable high dose for humans after this dose was found to be safe and active following three consecutive IM injections in the rabbit, the usual species for vaccine/adjuvant safety evaluation. 32 In the present immunogenicity study in macaques, no safety signal was observed in any of the vaccine groups, based on clinical observations, blood biochemistry and complete blood counts.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both systemic and dose site effects are likely due to the action of the immunostimulatory nature of MPL and/or the presence of l ‐tyrosine within the adjuvanted vaccine. More recently, a review of toxicity studies with 30 different adjuvanted vaccines showed common study findings of altered clinical pathology parameters (commonly raised blood neutrophil count and increased globulin levels, but also raised fibrinogen) and evidence of inflammation at the dose site (Baldrick, ). It was concluded that clinical pathological and injection site changes can be interpreted as related to an expected reaction after vaccine dosing, with generation of an immune response largely because of the presence of adjuvant, although direct vaccine antigen involvement was also occasionally demonstrated by the presence of a slightly increased inflammatory response seen over adjuvant treatment only.…”
Section: Discussionmentioning
confidence: 99%